(untitled) (Scientific journal of the Fergana State University, 2023)
In this article authors described the analysis of structure of primary disability of children’s population, conducted in Fergana region. Analysed specific gravity of primary disability of population at the place of residence and to the age-related-sexual groups of children. Principal reasons resulting in disability of children on the classes of illnesses are elucidated.